Il Caeremoniale nella storia della Messa Romana - Celiński, Łukasz (Warszawskie Studia Teologiczne, 2023)
Historical research must always pass through the critical study of sources. The historical value of a source can be assessed through comparison with other coeval sources, especially if they are of different type or origin, concerning, however, the same reality. The present study proposes an arrangement of the main papal and episcopal ceremonials of the Roman Rite area from the point of view of information related to the ritual performance of the Mass. Since the origins of the Roman ceremonial are to be found in the context of papal liturgies, our contribution also offers a contextual basis for the critical study of other sources such as, for example, medieval papal missals.